An annotated checklist of halacarid mites (Acari, Halacaridae) from India - Chatterjee, Tapas (Zootaxa, 2022)
A compilation of halacarid mite species (Halacaridae) from India has been carried out based on published records. Indian halacarid records were mostly found among algal habitats, some are also reported associated with pneumatophores and halophytes. Copidognathus is the most dominant genus with 19 species reported from the Indian coast. Reports of halacarid mites from Indian interstitial habitats are mostly doubtful and needs verification. Acarochelopodia delamarei, Copidognathus fabricii, Scaptognathus hallezi, Simognathus minutus should be excluded from Indian record. The real diversity and distribution of Indian halacarid fauna is far from being complete and future investigations may reveal further new taxa.